Exploring undergraduate students’ perceptions of food animal production and their sense of belonging in an introductory animal science course - Sullivan, Paxton; Smith, Colton; Machuca, Erica; Figan, Abigail; Mijares, Sage; Roman-Muniz, Noa; Cramer, Catie; Ahola, Jason; Stallones, Lorann; Edwards-Callaway, Lily (Frontiers in Animal Science, 2023)
New animal science undergraduates are further removed from agriculture than ever before, many coming from non-agricultural backgrounds lacking experience with food animals. In addition to beginning a degree program in which they have little experience, undergraduates face unique challenges during their transition to college, which could impact retention and success in their chosen major. The focal course, Food Animal Science: ANEQ 101, is an introductory animal science course composed primarily of first year animal science students. This course utilized experiential learning by implementing laboratories with dairy calves providing hands-on experience. Pre- and post-surveys were developed to assess students’ perceptions of food animal production, welfare, and sense of belonging in the Animal Science major at the beginning and end of this course that was characterized by hands-on opportunities; quantitative and qualitative analyses were performed on 114 paired survey responses. Respondents were mostly female (79%, n = 91), white (80.7%, n = 92), and from non-agricultural backgrounds (83.3%, n = 95). Despite only half (51.8%, n = 59) of respondents indicating that they had experience with food animals, most respondents indicated that they agreed being comfortable with food animal production (96.5%, n = 110) and working with food animals (95.6%; n = 109 ); agreement with these statements was similar in the post-survey (P > 0.05). More students agreed with the statement “In the United States, food animals are raised with an acceptable level of animal welfare” (P = 0.016) in the post-survey as compared with the pre-survey. In the pre- and post-survey, questions related to belonging garnered positive responses, consequently, there was no evidence that students’ sense of belonging in the major was altered during the course. Two free-response questions asked respondents to comment on their sense of belonging in the major. Thematic analysis of these answers identified themes related to belonging, including Learning and Curriculum, Career Goals and Aspirations, Passion for Working with Animals, Self-Assurance, and Community and Classroom Environment. The majority of students had positive views about production and their sense of belonging within the major highlighting the value of integrating experiential learning opportunities for students studying animal science.